(untitled) (Global Journal of Management and Business Research, 2023)
This study examined the contribution of mobile banking Informational Service on customer satisfaction Three elements of mobile banking i e information service was assessed to find out the role they play on customer satisfaction at CRDB Chamwino Branch bank The study adopted a cross sectional survey study design where data was collected at one point in time In addition to that both qualitative as well as quantitative approaches were employed in collecting data for triangulation Quantitative data was collected from 99 CRDB- Chamwino Branch customers through survey whereas the qualitative data were collected from CRDB officials through interviews Quantitative data was analyzed through SPSS where descriptive statistics as well as inferential and Logistic Regression model were used Furthermore the relationships between variables were established through binary Logistic Regression The qualitative data also were analyzed through Thematic Analysis technique Finding show there is positive significant relationship is also established between mobile banking information service and customer satisfaction with P- Value 0 002 The study concludes that mobile banking enhances customer satisfaction in commercial banks The study recommends for more efforts to be made in making sure mobile banking technology is enhanced Also more investment should be made in making sure that challenges associated with mobile banking technology are minimized